The Effect of Brand, Price, and Social Media on Car Tire Sales Volume at Station Tire Shop Grobogan - Yanto, Yudi; Hartina, Widya Endang; Djastuti, Indi (LifeSciFi, 2024)
Brand, price, and social media are significant determinants in customer purchasing decisions. Conversely, consumer comprehension of these issues is often flawed. This study seeks to examine the impact of brand, pricing, and social media on the sales volume of vehicle tires at a tire station in Grobogan. This Small Medium Enterprise (SME) has been operational for over nine years and employs diverse marketing methods to enhance projected sales. Brand attributes, competitive pricing, and active engagement on Facebook will be crucial in enhancing sales volume. The study employed quantitative data by administering questionnaires to 100 respondents and using Multiple Linear Regression Analysis to examine the link between independent factors (brand, price, social media) and the dependent variable (sales volume). The results indicate that brand, price, and social media significantly impact the enhancement of vehicle tire sales at the Tire Station enterprise.